Analisis Pencabutan Izin Usaha Dan Likuidasi Bank Di Indonesia - Kurniati, Herlina; Saputra, Kuryani; Tamza, Fristia Berdian (ASAS, 2021)
Indonesia's economy in the banking sector is experiencing ups and downs. There are times when it grows rapidly, and under certain conditions there are a number of banks experiencing problems and eventually being revoked their licenses. Revocation of business license is done as a last step in the efforts to heal the bank if the bank's difficulties interfere with its business continuity or endanger the banking system. It is a mandate from Law No. 7 of 1992 on Banking as amended by Law No. 10 of 1998. This paper wants to reveal the understanding, legal basis, liquidation factors to analasis revocation of business license and liquidation of banks in Indonesia. The method used in this study is the normative juridical approach method, in which the research conducted is by examining library research materials, which relate to the title being studied. This study concluded, first, OJK can revoke bpr business license because the condition of a bank endangers the banking system. Like the level of difficulty experienced in conducting business activities, the bank is unable to fulfill its obligations to other banks. Second, the bank has difficulties that jeopardize the continuity of its business and actions to overcome them are not enough to overcome the difficulties faced by the bank.Keywords: OJS, banking, liquidation